Mathematical model of student learning behavior with the effect of learning motivation and student social interaction - Mutiawati; Johar, Rahmah; Ramli, Marwan; Mailizar (Journal on Mathematics Education, 2022)
This study aims to determine the mathematical model of student learning behavior. The model is built by analogizing the spread of learning behavior with infectious diseases, which is called the SEIR model. The survey was conducted through filling out a questionnaire on the learning behavior of junior high school students with a population of 1,143 students. The results of the simulation model show that the peak of students' vulnerability to changes in learning behavior increases rapidly in the first two days and will be stable when passing the 150th day. The results of the simulation of the SEIR mathematical model with an incubation period of 365 days found that student learning behavior in Non-Boarding Schools will be stable in on day 198, while in Boarding Schools it will be stable on day 201. Infection cases in Boarding Schools fell to 0 on day 25 while in Non-Boarding Schools decreased on day 21, meaning that infections occurring in Boarding Schools were slower and more resistant long, meaning that the influence of the social environment is very significant on student learning behavior. This study also serves as material for policy formulation for the Aceh Provincial Government regarding the junior high school curriculum.